2021
DOI: 10.1002/essoar.10507068.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oceanic mesoscale eddy depletion catalyzed by internal waves

Abstract: The general circulation of the ocean is strongly constrained by the pathways that kinetic and available potential energy take from the basin-scale forces that inject them to centimeter scales, where they are depleted. To determine the ocean's response to future climate scenarios, these energy pathways, from forcing to dissipation, must be understood and quantified.Mesoscale eddies, with horizontal scales on the order of 100 km and timescales longer than many days, are well known as the dominant reservoir of ki… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In order to understand the multiscale nature of oceanic flows, while simultaneously resolving them in space and in time, we use a "coarse-graining" framework that is relatively new in physical oceanography (Aluie et al, 2018;Barkan et al, 2021;Busecke & Abernathey, 2019;Contreras et al, 2023;Haigh et al, 2021;Khani & Dawson, 2023;Khatri et al, 2023;Loose et al, 2023;Rai et al, 2021;Schubert et al, 2020;Srinivasan et al, 2019).…”
Section: Coarse-grainingmentioning
confidence: 99%
“…In order to understand the multiscale nature of oceanic flows, while simultaneously resolving them in space and in time, we use a "coarse-graining" framework that is relatively new in physical oceanography (Aluie et al, 2018;Barkan et al, 2021;Busecke & Abernathey, 2019;Contreras et al, 2023;Haigh et al, 2021;Khani & Dawson, 2023;Khatri et al, 2023;Loose et al, 2023;Rai et al, 2021;Schubert et al, 2020;Srinivasan et al, 2019).…”
Section: Coarse-grainingmentioning
confidence: 99%
“…In the LV case, Fer et al (2018) showed through high-resolution turbulence measurements that the background shear as well as near-inertial waves trapped by the negative vorticity of the LV are the dominant sources of kinetic energy loss. More generally, internal waves are suspected to drain a significant part of the energy of such mesoscale eddies (Barkan et al, 2021). These mechanisms are hardly resolved in the simulations discussed in the present paper, and are mainly controlled by the numerical parameterization (i.e., the vertical mixing induced by the KPP scheme).…”
mentioning
confidence: 66%
“…These months coincide with the maximum probability of internal waves observation in the Açores Islands (C. R. Jackson & Apel, 2004). Considering that internal waves promote the transfer of energy from the mesoscale to the submesoscale (Barkan et al, 2021), that their presence is more pronounced with tidal forcing, and that bFTLEs capture better the fine-scale and the GKDE the mesoscale transport dynamics; the tidal forcing is affecting differently the FTLE and GKDE diagnostics. We expect then an increase in the bFTLE fields (fine-scales) and a decrease in the GKDE fields (mesoscale) with the tidal forcing simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Several explanations could be behind these results. Barkan et al (2021) found that when internal wave forcing was used in their simulations (which could be analogous to the tidal forcing used here, as it creates a higher presence of internal waves), less mesoscale kinetic energy is present both in summer and winter. The energy is transferred towards submesoscale fronts and filaments, particularly in winter (Barkan et al, 2021), and this could impact on the coherence of the mesoscale eddies, reducing their capacity to trap particles in a higher presence of submesoscale structures (Haza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation